MODEL OF INTERACTION OF THE NETWORK CONTROL PLANE SDN WITH NETWORK MANAGEMENT SYSTEMS ACCORDING TO THE TMN CONCEPT - Konakhovych, Heorhii; Romanov, Anton (Science-based technologies, 2025)
To increase the efficiency of network operation, fully automate management, administration and technological maintenance processes, reduce the time to market for modern services, ensure the introduction of new technologies throughout the network, rather than their phased implementation at individual facilities, operators are beginning to widely use the technology of network resource virtualization. This approach is a distinctive feature of software-defined networking (SDN). The optimality of decisions made in such a network largely depends on the capabilities of the control plane in the SDN architecture. It should be noted that SDN networks will continue to operate for a long time in the environment of traditional networks, which telecom operators will use for several decades. Therefore, it is necessary to ensure the interaction of SDN networks with networks that use management systems based on the TMN concept. Here, the main control element is the OSS (Operation support system) block. In addition, it should be possible to include a human operator in the control loop, who will participate in solving poorly structured network management tasks that cannot be automated. The most difficult issues arise when solving the issues of ensuring the interaction of the SDN controller and control systems built on the basis of the TMN concept. Therefore, the paper details the architecture of the SDN control plane with consideration of the necessary elements that ensure interaction with control systems built using the TMN concept. A list of the necessary functional blocks in the architecture of the SDN controller, a list of tasks that they must solve, and their connections with other blocks are proposed. The elements that will ensure the collection of the necessary information that can be used as input data for solving management tasks are considered. The directions of formalization of management tasks are analyzed, using the indicators of telecommunication networks functioning as initial data. The requirements for a monitoring system for collecting the necessary initial data and an approximate algorithm for the interaction of elements to obtain optimal solutions in the process of network management are proposed.